Clinical Factors and Characteristics that Affect Prognosis of COVID-19 Patients (International Journal of Scientific Research and Management (IJSRM), 2022)
Background: COVID-19 disease has been linked to severe and deadly respiratory disease in various age groups. In team of COVID-19 disease prognosis and mortality, age is a key factor. The chance of mortality climbs from 0.66 percent to 7.8 percent in those over the age of 80. Males have a greater COVID-19 prevalence rate than females. Furthermore, even in the absence of additional comorbidities, sex was an essential biological determinant in prognosis and death risk among COVID-19 positive people. Another factor that influences the prognosis of COVID-19 illness is comorbidity. It’s critical to comprehend the clinical characteristics and variables that influence the prognosis of COVID-19 illness patients. Objective: To describe the clinical factors and characteristics that affect COVID-19 patients’ prognosis. Methods: Retrospective research performed at Queen Alia Military Hospital by examining clinical characteristics of hospitalized individuals with a verified diagnosis of COVID-19 disease, as confirmed by polymerase-chain-reaction (PCR) assay. The research comprised laboratory outcomes, demographic features, chest imaging, and clinical data. Participants were categorized into the progression category and the improvement/stabilization group. Results: A total of 51 participants with a mean age of 33.6 years were involved in the research. Forty-six participants (90.2%) were categorized as an improvement/stabilization group, and five patients were classified as a progression group (9.8%). Fever, diarrhea, breath shortness, and cough were the most common signs and symptoms. Significant differences were detected between groups concerning age, comorbid diseases (diabetes and hypertension), disease severity, length of stay in the hospital, WBCs, creatinine, total bilirubin, ALP, LDH, CRP, albumin, oxygen saturation, and pulmonary consolidation (P < 0.05). Moreover, multivariate logistic regression determined age (OR, 1.79; CI: .950 3.28; P = 0.035), diabetes (OR, 1.62; CI: 1.02 - 4.19; P 0.012), hypertension (OR, 1.13; CI: 1.04 - 3.62; P =0.023), increased creatinine (OR, 3.57; CI: 2.30 - 6.71; P = 0.01), and increased total bilirubin (OR, 2.82; CI: 1.72 - 3.28; P = 0.031) as risk factors for disease progression. Conclusion: Chronic disease and abnormal creatinine and bilirubin level including other factors contribute to poor prognosis of COVID-19 patients. This study shows that the clinical characteristics of the patient should be prioritized in disease management.